Farmers' motivational orientation toward participation in competence development projects: a self-determination theory perspective. Issue 2 (15th March 2017) - Charatsari, Chrysanthi; Lioutas, Evagelos D.; Koutsouris, Alex
ABSTRACT: Purpose: In this study, we use a self-determination theory (SDT) approach to understand farmers' attitudes toward, and intentions for, participation in competence development projects (CDP). Design/methodology/approach: By applying SDT, we developed two measures. The first one assessed the degree to which the three basic human psychological needs motivate farmers to engage in CDP, and the second concerned farmers' intrinsic and extrinsic motivation to seek knowledge through participation in CDP. Using data from two samples of farmers, we examined the effect of SDT needs and the influence of the different regulatory styles on individuals' decision to participate in CDP. Findings: Our findings indicated that participation in CDP is guided by the most internal forms of human motivation (identified, integrated, and intrinsic motivation), and that deficits in the needs for autonomy and competence predict farmers' decision to participate in CDP. Practical implications: These results stress the importance of designing CDP that promote self-directedness, emphasise choice rather than rewards, and generate the conditions that support farmers' autonomy. Theoretical implications: Our work suggests that the integration of social psychology into extension/education research can paint a more detailed picture of the way farmers interact with extension/education services. Originality/value: To the best of our knowledge, this is the first study that uses an SDT framework to examine farmers' motivation toward participation in CDP. Hence, this research opens a new realm for extension/education research, while it also contributes to the SDT literature by examining the role of self-determined motivation in a different life domain.